Femoral Bone Defects Managed With the Induced-Membrane Technique: Our Preferred Method of Treatment. Issue 1 (March 2016) - Stafford, Paul; Norris, Brent; Dadgar, Azad; Calder, Mark
Abstract : Although there are several options for treating femoral bone defects resulting from trauma or nonunion surgery, the induced-membrane technique is now our treatment of choice. The technique consists of 2 stages, and both are critical to successful treatment. Stage 1 begins with debridement of bone and soft tissue and concludes with insertion of a cement spacer, bone stabilization, and soft-tissue coverage. Stage 2 is typically delayed 4 weeks or more and consists of carefully opening the induced membrane, removing the spacer, and inserting bone graft. While many studies show excellent union rates, good outcomes are technique dependent and the treating surgeon should be careful to avoid common surgical pitfalls. In addition, patient biology must be considered and optimized to further improve union rates and outcomes.